2018
DOI: 10.1002/vnl.21644
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of plasticized polyvinyl butyral‐silica nanocomposite films and test production of laminated glass using films

Abstract: Plasticized polyvinyl butyral (PVB)-silica nanocomposite films were formed by mixing PVB ethanol solution and silica sol, which was prepared from tetraethyl orthosilicate. The nanocomposite films were colorless and transparent even though the content of silica was 70 wt%. The glass transition temperature of PVB in the silica 2.5 wt% nanocomposites was higher by about 108C than that of plasticized PVB. The PVB-silica nanocomposite films were applied as an interlayer for laminated glass. The laminated glass made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It was confirmed that the PVB-silica nanocomposite films containing less than 5 wt.% silica were appropriate for use as the interlayer for highperformance laminated glass. 16 Obradovic ´et al reported that the impregnation of p-aramid fabrics with PVB/ethanol solution which contained 30 wt.% AMEO silane modified silica nanoparticles produced improved mechanical properties in the body armor. 17 Cavitation is a phenomenon in which rapid changes of pressure in a liquid lead to the formation, growth and collapse of bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…It was confirmed that the PVB-silica nanocomposite films containing less than 5 wt.% silica were appropriate for use as the interlayer for highperformance laminated glass. 16 Obradovic ´et al reported that the impregnation of p-aramid fabrics with PVB/ethanol solution which contained 30 wt.% AMEO silane modified silica nanoparticles produced improved mechanical properties in the body armor. 17 Cavitation is a phenomenon in which rapid changes of pressure in a liquid lead to the formation, growth and collapse of bubbles.…”
Section: Introductionmentioning
confidence: 99%